Apples, apples, apples - Wallace, Nancy Elizabeth (Delray Beach, FL : Winslow Press, 2001)
Members of the Rabbit family visit an apple orchard, where they have fun picking apples and discovering their many uses. Includes a recipe for applesauce, directions for a craft activity, and sayings about apples.
G1
Keywords: Apples -- Fiction; Orchards -- Fiction; Rabbits -- Fiction